2021
DOI: 10.1111/bjso.12435
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐humanization enhances positive reactions to prosocial cross‐group interaction

Abstract: The present research investigated whether learning that an outgroup humanizes the ingroup (i.e., meta-humanization) enhances how people react to intergroup prosocial behaviours and their willingness to engage in intergroup contact. In three experiments conducted in two cultural contexts (Kosovo and North Macedonia; n = 601), we manipulated meta-humanization by informing participants that their ingroup is perceived to be as human as the outgroup by outgroup members. We compare this metahumanization condition wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
(74 reference statements)
3
17
0
Order By: Relevance
“…Normatively supported apologies could also fuel the perception that the outgroup perceives the ingroup as being more human-that is, meta-humanization (e.g., Kteily et al, 2016). Such suggestion is also consistent with recent findings showing that humanizing information from outgroup members affects victims' reactions to offers of help from outgroup members and their openness to intergroup reconciliation in post-conflict contexts (e.g., Borinca, Tropp, & Ofosu, 2021).…”
Section: Tablesupporting
confidence: 80%
“…Normatively supported apologies could also fuel the perception that the outgroup perceives the ingroup as being more human-that is, meta-humanization (e.g., Kteily et al, 2016). Such suggestion is also consistent with recent findings showing that humanizing information from outgroup members affects victims' reactions to offers of help from outgroup members and their openness to intergroup reconciliation in post-conflict contexts (e.g., Borinca, Tropp, & Ofosu, 2021).…”
Section: Tablesupporting
confidence: 80%
“…Second, our findings tie together previous research on the relationship between relative dehumanization and intergroup contact in relation to individuals’ conservative views on social, economic, and political matters. Despite research demonstrating that prejudice and dehumanization play distinct roles in intergroup relations (Borinca, Tropp, & Ofosu, 2021; Kteily et al, 2016), researchers have thus far investigated only prejudice’s moderating role on imagined interaction regarding intergroup attitudes and affect (Borinca, Falomir‐Pichastor, & Andrighetto, 2020). However, to our knowledge, no research has examined the moderating role of relative dehumanization among individuals with conservative views, despite the fact that the association between contact with outgroup members and dehumanization has been investigated (Bruneau et al, 2020; Capozza et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, positive contact (i.e., direct, extended, imagined, and virtual) was associated with reductions in the dehumanization of outgroup members (Bruneau et al, 2020; Capozza et al, 2014, 2017). Other related research has treated outgroup humanization as a predicting factor, and has shown that outgroup humanization (i.e., refined, cultured, rational, and logical) increased willingness for contact with outgroup members (Borinca, Falomir‐Pichastor, Andrighetto, & Halabi, 2021b) and that outgroup meta(de)humanization influenced reactions and understandings of an imagined prosocial intergroup interaction mediated by positive social emotions and feelings (Borinca, Tropp, & Ofosu, 2021). Of particular relevance for the present research, Bruneau et al (2020) suggested that the degree to which an individual initially dehumanizes an outgroup sets the stage for negative, ambiguous intergroup interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, meta-dehumanization appears to be corrigible: informing non-Muslim Westerners that Muslims in the Middle East consider them fully human reduces their blatant dehumanization of Muslims [104,107], particularly among those who perceive Muslims to be most threatening at baseline [107]. Other work in Kosovo and North Macedonia showed that participants told an outgroup considered their own group fully human were more likely to empathize with and accept the help of an outgroup member [108]. See Box 2 for other recent approaches to reducing dehumanization.…”
Section: Theoretical Challenges To Dehumanization Researchmentioning
confidence: 99%